2007
DOI: 10.1002/mrd.20562
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and localization of four connexins in the ovary of the ayu (Plecoglossus Altivelis)

Abstract: The post-vitellogenic oocytes of teleost fish are generally unresponsive to maturation-inducing hormone (MIH) until a luteinizing hormone (LH) surge stimulates sensitivity via the acquisition of oocyte-maturational competence (OMC). Heterologous gap junctions (GJs) between granulosa cells and the oocyte have been previously implicated in the regulation of oocyte maturation in various vertebrate species. Although heterologous GJ are present in ovarian follicles of ayu (Plecoglossus altivelis), their role in mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Next, we determined the site and stage of expression of each connexin messenger RNA (mRNA) in the ayu ovarian tissue using in situ and northern hybridization. Our results showed that Cx34.9 was expressed in both the follicle cells and the oocytes (Table 1), and was strongly expressed from the maturationally-incompetent stage through to mature stage (Table 1) [13]. In addition, Cx32.1 was expressed in both the follicle cells and the oocytes, and was particularly strongly expressed during the vitellogenic stage (Table 1) [13].…”
Section: Gj Protein Expression In Ayu Ovariesmentioning
confidence: 65%
See 4 more Smart Citations
“…Next, we determined the site and stage of expression of each connexin messenger RNA (mRNA) in the ayu ovarian tissue using in situ and northern hybridization. Our results showed that Cx34.9 was expressed in both the follicle cells and the oocytes (Table 1), and was strongly expressed from the maturationally-incompetent stage through to mature stage (Table 1) [13]. In addition, Cx32.1 was expressed in both the follicle cells and the oocytes, and was particularly strongly expressed during the vitellogenic stage (Table 1) [13].…”
Section: Gj Protein Expression In Ayu Ovariesmentioning
confidence: 65%
“…Our results showed that Cx34.9 was expressed in both the follicle cells and the oocytes (Table 1), and was strongly expressed from the maturationally-incompetent stage through to mature stage (Table 1) [13]. In addition, Cx32.1 was expressed in both the follicle cells and the oocytes, and was particularly strongly expressed during the vitellogenic stage (Table 1) [13]. By contrast, the expression of Cx44.1 and Cx44.2 was confirmed only in oocytes, and these connexins were present at constant levels during all stages, including after ovulation (Table 1) [13].…”
mentioning
confidence: 89%
See 3 more Smart Citations